2018
DOI: 10.25159/2520-5293/1590
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Treatment and Retention to Care of Adult Patients on Antiretroviral Therapy

Abstract: The introduction of antiretroviral therapy came as a relief to people living with HIV and AIDS as it improved their quality of life and chances of survival, and delayed the progression to AIDS. Maintaining high adherence levels to antiretroviral therapy remains a challenge for many, yet strict adherence and retention to care are critical for the successful suppression of the human immunodeficiency virus. The objective of the study was to determine factors that influence adherence and retention to care for adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This finding is in line with other studies that have reported having a handbag to have pills all the time as the preferred ART storage by patients. 40 , 41 , 42 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in line with other studies that have reported having a handbag to have pills all the time as the preferred ART storage by patients. 40 , 41 , 42 …”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with other studies that have reported having a handbag to have pills all the time as the preferred ART storage by patients. 40,41,42 Side effects are an important predictor of poor adherence, and cumulative toxicity associated with ART, especially in second-line regimens. 43,44,45 We found that participants with VLF were more likely to have treatment-related side effects.…”
Section: Discussionmentioning
confidence: 99%